OVEREXPLOITATION OF GROUNDWATER RESOURCES IN THE COASTAL AQUIFER SYSTEM OF ARGOLIS - Mitropapas, A.; Koumantakis, I.; Vasileiou, E.; Perdikaki, M.; Kallioras, A. (Bulletin of the Geological Society of Greece, 2016)
Intense abstraction of groundwater resources in the coastal aquifer system of Argolis is investigated since the late 1950’s. The increasing water demands due to the agricultural development of the area (mainly citrus trees) during the last years, in combination with the touristic growth, has led to the overexploitation of groundwater resources of the coastal aquifer system of Argolis. This paper presents the piezometric conditions in the plain of Argos during the period between 1986 and 2014, analysing the fluctuations of groundwater levels and highlighting the problem of seawater intrusion in the study area. In October 2014, measurements were made in app. 160 wells and drills which are located within the boundaries of the granular aquifer of the study area. Selected piezometric maps are presented, which demonstrate the problem of overexploitation of groundwater in the plain of Argos.